PENGARUH SUKU BUNGA KEBIJAKAN, MONEY SUPPLY, DAN PAJAK PERTAMBAHAN NILAI TERHADAP INFLASI DI INDONESIA - Edgar, Khairil; Kosasih, Chelsea Valencia; Sutjahjo, Alexa Priscilla (Accounting Study Program, Universitas Ciputra Surabaya, 2026)
Price stability is commonly assessed through the behavior of inflation, making it one of the key indicators used to evaluate the overall condition of an economy. When inflation exhibits continuous fluctuations, maintaining macroeconomic stability becomes more challenging and requires policy responses that are both effective and well integrated. In this context, the interaction between monetary and fiscal policy instruments becomes particularly important in shaping inflation dynamics. This study therefore investigates how several policy variables influence inflation in Indonesia during the period 2015 to 2024, specifically focusing on the policy interest rate, the broad money supply (M2), and the Value Added Tax (VAT) policy. The analysis adopts a quantitative framework using monthly time series data sourced from Bank Indonesia, Statistics Indonesia, and the Ministry of Finance of the Republic of Indonesia. Empirically, the relationship among these variables is estimated through a multiple linear regression model, while robust standard error are applied to strengthen the reliability of the estimates in the presence of potential violations of classical regression assumptions. The results from the joint significance test demonstrate that the policy rate, money supply, and VAT policy collectively exert a statistically significant influence on inflation. However, further examination through partial tests indicates that the policy interest rate does not significantly affect inflation, whereas variations in money supply and the implementation of VAT policy contribute more strongly to changes in inflation. These findings indicate that inflation dynamics in Indonesia during the observed period are more closely associated with liquidity conditions and fiscal policy measures than with the policy interest rate alone. Consequently, inflation management cannot depend solely on a single policy instrument. Effective and sustained price stability therefore requires strong coordination between monetary and fiscal authorities in responding to increasingly complex economic developments.